‘To Ugi’ in the Bugis-Wajo Kinship System: Language, Culture, and the Shaping of Social Identity - Basri, Rina Khuzaimah; Zakiyah, Millatuz; Arifin, Ferdi (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2025)
This study observes the linguistic diversity of a community to find out the cultural inheritance for the next generation in Wajo Regency, South Sulawesi. The objectives of this study are to describe the meaning of the kinship system in Bugis society in the marriage custom, second to describe the inheritance system of the perception of To Ugi in Wajo district, South Sulawesi, and third to describe the nickname “To Ugi” in the kinship system. A descriptive qualitative approach was used to investigate data sources by describing the symptoms arising from the meaning of To Ugi in the Bugis Society in Wajo District, Tempe. Research data were collected from observation and interviews with four informants, one of whom was a Wajo traditional leader. The results showed that the Bugis-Wajo kinship system found 10 series of traditional processions, forbidden marriages, the main standards of the family that have to be followed when people enter marriage, and the stages before marrying based on the word assiajingeng. Kinship in Wajo is classified as parental by following the social system of the father and mother or the lineage of both parents. The 2:1 cultural inheritance sharing system between men and women benefits those who do not understand the kinship laws in Wajo Regency. The contribution of this study is that it opens up further opportunities for exploration into the relationship between language, social structure, and the formation of social classes within traditional communities, as well as the potential integration of local wisdom into character education and sustainable development.